Sustainable biodiesel synthesis from oleic acid: kinetic study with carbonized bambara nutshell catalyst - Kefas, Haruna Mavakumba; Abubakar, Abdulhalim Musa; Aliyu, Muhammad Jimada; Bulus, Raymond; Stojchevski, Martin; Soomro, Suhail Ahmed (Latin American Journal of Energy Research, 2024)
Mineral content in bambara nutshell (BNS) can act as active sites for catalysis, while the protein content can be carbonized to produce support structures for the catalyst. BNS char based solid acid catalyst is produced in this study for biodiesel (FAME) production, using oleic acid esterified with methanol. The objective of the study is to determine the order of reaction ran at 50-65 for 180 min utilizing the integral kinetic rate expression. It also involves analyzing the rate constants obtained, so as to use it to estimate the activation energy () and pre-exponential factors () necessary to describe the mechanism of the reaction. Findings show that, the presence of -OH functional group in BNS makes it a good candidate for biodiesel production. Faster reaction and conversion to FAME product ( 52%) occurred at 65. The first-order model almost describes the experimental data at 60 and R2 = 0.9850, only that it has an intercept, which is not typical of the model; although not a sufficient reason to discard it. In this study, the best model fitted is second-order at the lowest temperature analyzed (i.e., 50 with rate constant, = 2 L/mol.min L/mol.min), due to faster reaction rate described by its higher value of 6.973 L/mol.min. However, the first-order rate’s low energy requirement ( 51.63 kJ/mol), was the reason for its sluggishness compared to second-order 65.17 kJ/mol; which explains the reason why the choice of the best model could go both ways, if energy efficiency is considered. Despite the performance of the oleic acid, which is favorably described by the first- and second-order rate, its conversion to biodiesel is moderately significant.